The Effect of Promotion and Store Atmosphere on Purchasing Decisions - Nurika, Intan; Junaida, Erni; Bulan, T. Putri Lindung (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the effect of promotion and store atmosphere on purchasing decisions at Toko Mas Indah, Langsa City. A sample of 96 respondents. The analytical method uses multiple linear regression, t test, F test and coefficient of determination test. The results of the t test state that promotional factors have a significant influence on purchasing decisions and store atmosphere has a significant influence on purchasing decisions. The results of the F test show that promotions and store atmosphere have a significant effect on purchasing decisions. The results of the coefficient of determination test (adjusted R2) obtained a value of 0.737 or 73.7%, this means that promotional variables, store atmosphere and service quality influence purchasing decisions. While the remaining 26.3% is influenced by other variables not examined in this study.